CRIMINAL LAW CONSIDERATIONS (Ratio Decidendi) - Prayitno Iman Santosa (Indonesian Journal of Law and Policy Studies, 2020)
Judicial practice in Indonesia, judging from the decisions of criminal cases, generally judges give legal considerations only to prove the elements of a criminal offense. In contrast, the determination of the crime is not objectively considered, and most are merely considerations of incriminating and mitigating matters. On the other hand, the judge has absolute authority in imposing a crime; the judge's freedom is guaranteed by law. The supreme power of judges who are used freely without objective measures has the potential to produce corrupt decisions and injustices. Criminal objectives must be aligned with legal goals, namely to realize penalties that guarantee legal certainty, justice, and expediency. Ideally, good sentences reflect the three purposes of the law.